Low-warpage glass fiber reinforced nylon material
By adding appropriate amounts of glass fiber, coupling agent and other components to the nylon material and using a twin screw extruder for melt blending, the nylon material has high warpage, uneven surface, low toughness and combustion speed. The problem of slow and poor flame retardant effect achieves the smooth surface, high strength toughness and good flame retardant performance of the material.
Patent Information
- Application Number
- CN202411805768.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nylon materials have high warpage, uneven surface, low toughness, slow combustion speed and poor flame retardant effect.
Using low-warping glass fiber reinforced nylon material, by adding glass fiber, coupling agent, processing aid, interface reinforcement, inorganic flame retardant and lubricant to the nylon resin, it is melted through stirred tank mixing and twin screw extruder Blend and extrusion granulation to form a material with a flat surface and high strength toughness.
It significantly reduces the warpage of the material, makes the surface smooth, strengthens the strength and toughness of the material, increases the combustion speed, and enhances the flame retardant effect.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of reinforced nylon materials, in particular to a low-warpage glass fiber reinforced nylon material. Background Art
[0002] Reinforced nylon material is to add a certain amount of reinforcing material (such as glass fiber, carbon fiber, etc.) to the nylon resin matrix, and make the two closely combined through a specific preparation process, so as to significantly improve the mechanical properties, heat resistance, wear resistance, and dimensional stability of nylon. Low-warpage glass fiber reinforced nylon material has a series of excellent characteristics, which make it widely used in many fields. Glass fiber is one of the most commonly used reinforcing materials in reinforced nylon. It has the advantages of light weight, high strength, good heat resistance, and strong corrosion resistance. The addition of glass fiber can significantly improve the tensile strength, bending strength, impact strength and other mechanical properties of nylon, and reduce the water absorption and shrinkage of the material. However, the existing nylon material has a warpage, uneven surface, low toughness, low burning speed, and poor flame retardant effect.
[0003] The defects of existing reinforced nylon materials are:
[0004] 1. Patent document CN113943435A discloses a flame-retardant, low-warping, solder-resistant nylon glass fiber reinforced composite material, "including the following components by weight: 30-46 parts of nylon 66 resin, 22-31 parts of glass fiber with an elliptical cross-section, 3-5 parts of molybdenum disulfide, 17-22 parts of brominated polystyrene, 4-8 parts of antimony trioxide, 3-5 parts of zinc oxide, 4-6 parts of nano-barium sulfate, 1-3 parts of compatibilizer, 0.2-0.5 parts of antioxidant, 0.2-0.5 parts of nucleating agent, 0.2-0.5 parts of lubricant; the composite material has the characteristics of good flame retardancy, aging resistance, high temperature solder resistance, etc.", but the existing nylon material has a warpage, uneven surface, low toughness, low burning speed and poor flame retardant effect;
[0005] 2. Patent document CN117866428A discloses a low-warping, high-toughness, weather-resistant glass fiber reinforced nylon composite material and its preparation method, "including the following components by weight: 20-40 parts of nylon resin, 40-60 parts of chopped glass fiber, 15-30 parts of ground glass fiber, 0.5-2 parts of coupling agent, 0.5-2 parts of functional black masterbatch, and 0.1-2 parts of processing aid. The present invention adopts a method of combining ground glass fiber and urea-based silane coupling agent to make the glass fiber reinforced nylon composite material with a filling amount of 60wt% % or more, greatly improving the mechanical properties of composite materials. By combining with functional black masterbatch, the processing performance of the material is significantly improved. The particles are smooth and burr-free, and there is no lack of glue in the injection molding process. The obtained molded products have low warpage, high weather resistance, high strength and high toughness. They can directly replace metal spray paint and be used as parts such as skylight cantilevers, bases, elevator guide rail sliders, luggage racks, etc., expanding the application range of nylon-based composite materials. However, the existing nylon materials have a high warpage, uneven surface, low toughness, low burning speed and poor flame retardant effect.
[0006] 3. Patent document CN105623249A discloses a high-gloss and high-strength nylon / organic long glass fiber composite material and its preparation method, "nylon 6 is 50-70%, organic long glass fiber masterbatch is 20-40%, anti-floating fiber masterbatch is 2-5%, nano calcium carbonate is 1-10%, and color masterbatch is 2-4%; the organic long glass fiber masterbatch is an alkali-free long glass fiber that has been organically coated, and the coating includes a coupling agent, high-flow nylon and polyethylene terephthalate fiber, and the aspect ratio of the long glass fiber is 100-300. The present invention adopts Organic long glass fiber masterbatch, anti-floating fiber masterbatch, nano calcium carbonate and other modified reinforced nylon materials, through the coupling modification of long glass fiber, nylon and polyethylene terephthalate resin film reaction coating, effectively reduce the surface polarity of glass fiber, improve the compatibility of glass fiber and nylon; at the same time, the surface coated organic film and anti-floating fiber masterbatch synergistically reduce the floating fiber and warping phenomenon of glass fiber on the surface of composite materials, improve the finish, and enhance the strength and toughness of the material. However, the existing nylon material has a high warpage, uneven surface, low toughness, low burning speed and poor flame retardant effect;
[0007] 4. Patent document CN108102363A discloses a high temperature resistant and low warping nylon composite material for automobile engine hood, "comprising the following components by mass: 40-80 parts of nylon 66, 10-30 parts of glass fiber, 10-30 parts of mineral filler, 5-9 parts of TPO, 0.5-2 parts of lubricant, 0.1-0.8 parts of antioxidant, 0.2-1.7 parts of heat stabilizer, and 0.7-2.5 parts of dye. By adopting the above technical scheme, nylon 66 has higher thermal stability than other ordinary nylons. Secondly, the addition of heat stabilizer can further enhance the thermal stability of nylon 66. In addition, TPO is a kind of TPE, which has good elasticity and can effectively enhance the self-healing ability of nylon 66, thereby reducing the probability of warping of nylon materials", but the existing nylon materials have uneven warping surface, low toughness, low burning speed and poor flame retardant effect. Summary of the invention
[0008] The purpose of the present invention is to provide a low-warpage glass fiber reinforced nylon material to solve the technical problems of the existing nylon material mentioned in the above background technology, such as the uneven surface of the material, low toughness, low burning speed and poor flame retardant effect.
[0009] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a low-warpage glass fiber reinforced nylon material, comprising the following material components by mass: 30-45 parts of nylon resin, 3-8 parts of glass fiber, 10-20 parts of coupling agent, 12-28 parts of processing aid, 8-16 parts of interface enhancer, 2-6 parts of inorganic flame retardant, 3-8 parts of lubricant, and 2-7 parts of reinforcing agent. The material components are mixed evenly in a stirring kettle, and a mixture A is formed after the kettle is mixed evenly. The mixture A is put into the main feeding hopper of a twin-screw extruder, the ground glass fiber is fed through the front feeding hopper, and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded into granules by a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated on the surface of the glass fiber by a hydrofluoric acid spraying method to improve the roughness of the surface of the glass fiber, thereby enhancing the interface bonding force between the glass fiber and the nylon.
[0010] Preferably, the interface enhancer is one of organic silicon, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing the interfacial adhesion of the material. The thin film improves the mechanical properties and chemical stability of the material.
[0011] Preferably, the nylon resin is one of PA6, PA66, PA56 or PA6 / 66, and the viscosity of the nylon resin is 1.8 to 2.4.
[0012] Preferably, the glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warpage. The chopped glass fiber is used to improve the strength and rigidity of the material, and the milled glass fiber helps to improve the fluidity and processing properties of the material.
[0013] Preferably, the coupling agent is a urea-based silane coupling agent to improve the interfacial bonding between the glass fiber and the nylon resin, thereby improving the overall performance of the composite material.
[0014] Preferably, the processing aids are stabilizers S-EED, 1098, 168, H10, H318 and modified ethylenebisfatty acid amide TAF, silicone, erucic acid amide, stearate, EBS, oxidized PE wax to improve the processing performance and stability of the material.
[0015] Preferably, the flame retardant is ammonium polyphosphate flame retardant DHPA-6621 or hypophosphite flame retardant FR701.
[0016] Preferably, the melt blending temperature is 200-500°C.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention is equipped with 35 parts of nylon resin, 4 parts of glass fiber, 12 parts of coupling agent, 14 parts of processing aid, 10 parts of interface enhancer, 3 parts of inorganic flame retardant, 3 parts of lubricant, and 2 parts of reinforcing agent, and the material components are mixed evenly in a stirring kettle, and the kettle is mixed evenly to form a mixture A, and the mixture A is put into the main feeding hopper of the twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper, and the short glass fiber is fed through the rear feeding hopper, and melt blending and extrusion granulation are carried out through the co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material, so that the warpage of the nylon material of the present invention is achieved, the surface of the material is flat, and the strength and toughness are increased;
[0019] 2. The present invention is equipped with 38 parts of nylon resin, 5 parts of glass fiber, 13 parts of coupling agent, 15 parts of processing aid, 12 parts of interface enhancer, 4 parts of inorganic flame retardant, 4 parts of lubricant and 3 parts of reinforcing agent, the material components are mixed evenly in a stirring kettle, and a mixture A is formed after the mixture is evenly mixed in the kettle. The mixture A is put into the main feeding hopper of a twin-screw extruder, the ground glass fiber is fed through the front feeding hopper, and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded into granules by a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material, thereby achieving a low combustion rate and improved flame retardant effect of the nylon material of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] Embodiment 1: An embodiment provided by the present invention: A low-warpage glass fiber reinforced nylon material, comprising the following material components by mass: 35 parts of nylon resin, 4 parts of glass fiber, 12 parts of coupling agent, 14 parts of processing aid, 10 parts of interface enhancer, 3 parts of inorganic flame retardant, 3 parts of lubricant, and 2 parts of enhancer. The material components are mixed evenly in a stirring kettle, and a mixture A is formed after the mixture is evenly mixed in the kettle. The mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded and granulated through a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with a hydrofluoric acid spraying method on the surface of the glass fiber to improve the roughness of the surface of the glass fiber, thereby enhancing the interface bonding force between the glass fiber and the nylon. The interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing The interfacial adhesion of the material, the film improves the mechanical properties and chemical stability of the material, the nylon resin is one of PA6, PA66, PA56 or PA6 / 66, the viscosity of the nylon resin is 1.8-2.4, the glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warpage, the chopped glass fiber is used to improve the strength and rigidity of the material, the milled glass fiber helps to improve the fluidity and processing performance of the material, the coupling agent is a urea-based silane coupling agent to improve the interfacial bonding between the glass fiber and the nylon resin, and improve the overall performance of the composite material, the processing aids are stabilizers S-EED, 1098, 168, H10, H318 and modified ethylene bis fatty acid amide TAF, silicone, erucamide, stearate, EBS, oxidized PE wax to improve the processing performance and stability of the material, the flame retardant is ammonium polyphosphate flame retardant DHPA-6621 or hypophosphite flame retardant FR701, and the temperature of melt blending is 200-500°C.
[0022] Embodiment 2: An embodiment provided by the present invention: A low-warpage glass fiber reinforced nylon material, comprising the following material components by mass: 38 parts of nylon resin, 5 parts of glass fiber, 13 parts of coupling agent, 15 parts of processing aid, 12 parts of interface enhancer, 4 parts of inorganic flame retardant, 4 parts of lubricant, and 3 parts of reinforcing agent. The material components are mixed evenly in a stirring kettle, and a mixture A is formed after the mixture is evenly mixed in the kettle. The mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded and granulated through a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with a hydrofluoric acid spraying method on the surface of the glass fiber to improve the roughness of the surface of the glass fiber, thereby enhancing the interface bonding force between the glass fiber and the nylon. The interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing The interfacial adhesion of the material, the film improves the mechanical properties and chemical stability of the material, the nylon resin is one of PA6, PA66, PA56 or PA6 / 66, the viscosity of the nylon resin is 1.8-2.4, the glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warpage, the chopped glass fiber is used to improve the strength and rigidity of the material, the milled glass fiber helps to improve the fluidity and processing performance of the material, the coupling agent is a urea-based silane coupling agent to improve the interfacial bonding between the glass fiber and the nylon resin, and improve the overall performance of the composite material, the processing aids are stabilizers S-EED, 1098, 168, H10, H318 and modified ethylene bis fatty acid amide TAF, silicone, erucamide, stearate, EBS, oxidized PE wax to improve the processing performance and stability of the material, the flame retardant is ammonium polyphosphate flame retardant DHPA-6621 or hypophosphite flame retardant FR701, and the temperature of melt blending is 200-500°C.
[0023] Embodiment 3: An embodiment provided by the present invention: a low-warpage glass fiber reinforced nylon material, comprising the following material components by mass: 38 parts of nylon resin, 6 parts of glass fiber, 16 parts of coupling agent, 20 parts of processing aid, 14 parts of interface enhancer, 3 parts of inorganic flame retardant, 4 parts of lubricant, and 3 parts of reinforcing agent. The material components are mixed evenly in a stirring kettle, and a mixture A is formed after the mixture is evenly mixed in the kettle. The mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded and granulated through a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with a hydrofluoric acid spraying method on the surface of the glass fiber to improve the roughness of the surface of the glass fiber, thereby enhancing the interface bonding force between the glass fiber and the nylon. The interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing The interfacial adhesion of the material, the film improves the mechanical properties and chemical stability of the material, the nylon resin is one of PA6, PA66, PA56 or PA6 / 66, the viscosity of the nylon resin is 1.8-2.4, the glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warpage, the chopped glass fiber is used to improve the strength and rigidity of the material, the milled glass fiber helps to improve the fluidity and processing performance of the material, the coupling agent is a urea-based silane coupling agent to improve the interfacial bonding between the glass fiber and the nylon resin, and improve the overall performance of the composite material, the processing aids are stabilizers S-EED, 1098, 168, H10, H318 and modified ethylene bis fatty acid amide TAF, silicone, erucamide, stearate, EBS, oxidized PE wax to improve the processing performance and stability of the material, the flame retardant is ammonium polyphosphate flame retardant DHPA-6621 or hypophosphite flame retardant FR701, and the temperature of melt blending is 200-500°C.
[0024] Embodiment 4: An embodiment provided by the present invention: A low-warpage glass fiber reinforced nylon material, comprising the following material components by mass: 40 parts of nylon resin, 5 parts of glass fiber, 17 parts of coupling agent, 23 parts of processing aid, 11 parts of interface enhancer, 5 parts of inorganic flame retardant, 5 parts of lubricant, and 3 parts of reinforcing agent. The material components are mixed evenly in a stirring kettle, and a mixture A is formed after the mixture is evenly mixed in the kettle. The mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded and granulated through a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with a hydrofluoric acid spraying method on the surface of the glass fiber to improve the roughness of the surface of the glass fiber, thereby enhancing the interface bonding force between the glass fiber and the nylon. The interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing The interfacial adhesion of the material, the film improves the mechanical properties and chemical stability of the material, the nylon resin is one of PA6, PA66, PA56 or PA6 / 66, the viscosity of the nylon resin is 1.8-2.4, the glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warpage, the chopped glass fiber is used to improve the strength and rigidity of the material, the milled glass fiber helps to improve the fluidity and processing performance of the material, the coupling agent is a urea-based silane coupling agent to improve the interfacial bonding between the glass fiber and the nylon resin, and improve the overall performance of the composite material, the processing aids are stabilizers S-EED, 1098, 168, H10, H318 and modified ethylene bis fatty acid amide TAF, silicone, erucamide, stearate, EBS, oxidized PE wax to improve the processing performance and stability of the material, the flame retardant is ammonium polyphosphate flame retardant DHPA-6621 or hypophosphite flame retardant FR701, and the temperature of melt blending is 200-500°C.
[0025] Embodiment 5: An embodiment provided by the present invention: a low-warpage glass fiber reinforced nylon material, comprising the following material components by mass: 40 parts of nylon resin, 7 parts of glass fiber, 18 parts of coupling agent, 27 parts of processing aid, 15 parts of interface enhancer, 6 parts of inorganic flame retardant, 7 parts of lubricant, and 6 parts of reinforcing agent. The material components are mixed evenly in a stirring kettle, and a mixture A is formed after the mixture is evenly mixed in the kettle. The mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded and granulated through a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with a hydrofluoric acid spraying method on the surface of the glass fiber to improve the roughness of the surface of the glass fiber, thereby enhancing the interface bonding force between the glass fiber and the nylon. The interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing The interfacial adhesion of the material, the film improves the mechanical properties and chemical stability of the material, the nylon resin is one of PA6, PA66, PA56 or PA6 / 66, the viscosity of the nylon resin is 1.8-2.4, the glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warpage, the chopped glass fiber is used to improve the strength and rigidity of the material, the milled glass fiber helps to improve the fluidity and processing performance of the material, the coupling agent is a urea-based silane coupling agent to improve the interfacial bonding between the glass fiber and the nylon resin, and improve the overall performance of the composite material, the processing aids are stabilizers S-EED, 1098, 168, H10, H318 and modified ethylene bis fatty acid amide TAF, silicone, erucamide, stearate, EBS, oxidized PE wax to improve the processing performance and stability of the material, the flame retardant is ammonium polyphosphate flame retardant DHPA-6621 or hypophosphite flame retardant FR701, and the temperature of melt blending is 200-500°C.
[0026] Comparative experiment:
[0027] The difference between Comparative Example 1 and Example 1 is that;
[0028] 35 parts of nylon resin, 4 parts of glass fiber, 12 parts of coupling agent, 14 parts of processing aid, 10 parts of interface enhancer, 3 parts of inorganic flame retardant, 3 parts of lubricant, 2 parts of reinforcing agent, the material components are mixed evenly in a stirring kettle, and the mixture A is formed after the mixture is evenly mixed in the kettle. The mixture A is put into the main feeding hopper of the twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded into granules through the co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with hydrofluoric acid spraying to improve the roughness of the glass fiber surface, thereby enhancing the glass fiber. The interface bonding force between the fiber and nylon, the interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing the interface adhesion of the material. The film improves the mechanical properties and chemical stability of the material. The nylon resin is one of PA6, PA66, PA56 or PA6 / 66. The viscosity of the nylon resin is 1.8 to 2.4. The glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warping. Chopped glass fiber is used to improve the strength and rigidity of the material, and milled glass fiber helps to improve the fluidity and processing performance of the material.
[0029] The difference between Comparative Example 1 and Example 2 is that;
[0030] 38 parts of nylon resin, 5 parts of glass fiber, 13 parts of coupling agent, 15 parts of processing aid, 12 parts of interface enhancer, 4 parts of inorganic flame retardant, 4 parts of lubricant and 3 parts of reinforcing agent are mixed evenly in a stirring kettle to form a mixture A. Mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded into granules through a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with hydrofluoric acid spraying to improve the roughness of the glass fiber surface, thereby enhancing the glass fiber. The interface bonding force between the fiber and nylon, the interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing the interface adhesion of the material. The film improves the mechanical properties and chemical stability of the material. The nylon resin is one of PA6, PA66, PA56 or PA6 / 66. The viscosity of the nylon resin is 1.8 to 2.4. The glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warping. Chopped glass fiber is used to improve the strength and rigidity of the material, and milled glass fiber helps to improve the fluidity and processing performance of the material.
[0031] The difference between Comparative Example 1 and Example 3 is that;
[0032] 38 parts of dragon resin, 6 parts of glass fiber, 16 parts of coupling agent, 20 parts of processing aid, 14 parts of interface enhancer, 3 parts of inorganic flame retardant, 4 parts of lubricant and 3 parts of reinforcing agent are mixed evenly in a stirring kettle to form a mixture A. Mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded into granules through a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with hydrofluoric acid spraying to improve the roughness of the glass fiber surface, thereby enhancing the glass fiber. The interface bonding force between glass fiber and nylon, the interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between glass fiber and nylon resin, thereby enhancing the interface adhesion of the material. The film improves the mechanical properties and chemical stability of the material. The nylon resin is one of PA6, PA66, PA56 or PA6 / 66. The viscosity of the nylon resin is 1.8-2.4. The glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warping. Chopped glass fiber is used to improve the strength and rigidity of the material, and milled glass fiber helps to improve the fluidity and processing performance of the material.
[0033] The difference between Comparative Example 1 and Example 4 is that;
[0034] 40 parts of nylon resin, 5 parts of glass fiber, 17 parts of coupling agent, 23 parts of processing aid, 11 parts of interface enhancer, 5 parts of inorganic flame retardant, 5 parts of lubricant and 3 parts of reinforcing agent are mixed evenly in a stirring kettle to form a mixture A. Mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded into granules by a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with hydrofluoric acid spraying to improve the roughness of the glass fiber surface, thereby enhancing the glass fiber. The interface bonding force between the fiber and nylon, the interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing the interface adhesion of the material. The film improves the mechanical properties and chemical stability of the material. The nylon resin is one of PA6, PA66, PA56 or PA6 / 66. The viscosity of the nylon resin is 1.8 to 2.4. The glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warping. Chopped glass fiber is used to improve the strength and rigidity of the material, and milled glass fiber helps to improve the fluidity and processing performance of the material.
[0035] The difference between Comparative Example 1 and Example 5 is that;
[0036] 40 parts of nylon resin, 7 parts of glass fiber, 18 parts of coupling agent, 27 parts of processing aid, 15 parts of interface enhancer, 6 parts of inorganic flame retardant, 7 parts of lubricant and 6 parts of reinforcing agent are mixed evenly in a stirring kettle to form a mixture A. Mixture A is put into the main feeding hopper of a twin-screw extruder, and the ground glass fiber is fed through the front feeding hopper and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded into granules by a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated with hydrofluoric acid spraying to improve the roughness of the glass fiber surface, thereby enhancing the glass fiber. The interface bonding force between the fiber and nylon, the interface enhancer is one of silicone, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing the interface adhesion of the material. The film improves the mechanical properties and chemical stability of the material. The nylon resin is one of PA6, PA66, PA56 or PA6 / 66. The viscosity of the nylon resin is 1.8 to 2.4. The glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warping. Chopped glass fiber is used to improve the strength and rigidity of the material, and milled glass fiber helps to improve the fluidity and processing performance of the material.
[0037] The nylon materials of Examples 1, 2, 3, 4, and 5 of the present invention and the conventional nylon material (Comparative Example 1) were subjected to a burning speed test and a warpage test, respectively, and their values were calculated and statistically analyzed, and the results are shown in Table 1:
[0038] Spend Warpage (%) Burning speed (mm / min) Example 1 5 8 Example 2 6 7 Example 3 4 9 Example 4 5 7 Example 5 5 8 Comparative Example 1 10 15
[0039] From the data in Table 1, it can be seen that the warpage of the nylon material in Example 1, Example 2, Example 3, Example 4 and Example 5 of the present invention are 5, 6, 4, 5 and 5 respectively, which are significantly lower than the warpage of the nylon material in Comparative Example 1. Therefore, it is explained that the warpage of the nylon material of the present invention makes the surface of the material smooth and increases the strength and toughness.
[0040] From the data in Table 1, it can be seen that the burning rates of the nylon materials in Examples 1, 2, 3, 4 and 5 of the present invention are 8, 7, 9, 7 and 8 respectively, which are significantly lower than the burning rate of the nylon material in Comparative Example 1. Therefore, it is shown that the burning rate of the nylon material of the present invention improves the flame retardant effect.
[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A low-warpage glass fiber reinforced nylon material, characterized by: The material components are calculated by weight: 30-45 parts of nylon resin, 3-8 parts of glass fiber, 10-20 parts of coupling agent, 12-28 parts of processing aid, 8-16 parts of interface enhancer, 2-6 parts of inorganic flame retardant, 3-8 parts of lubricant and 2-7 parts of reinforcing agent. The material components are mixed evenly in a stirring kettle to form a mixture A. The mixture A is put into the main feeding hopper of a twin-screw extruder, the ground glass fiber is fed through the front feeding hopper, and the short-cut glass fiber is fed through the rear feeding hopper. The mixture is melt-blended and extruded into granules through a co-rotating twin-screw extruder to obtain a low-warpage glass fiber reinforced nylon material. The glass fiber is treated on the surface by a hydrofluoric acid spraying method to improve the roughness of the glass fiber surface, thereby enhancing the interface bonding force between the glass fiber and nylon.
2. The low-warpage glass fiber reinforced nylon material according to claim 1, characterized in that: The interface enhancer is one of organic silicon, titanate, and silane coupling agent. The interface enhancer forms a thin film between the glass fiber and the nylon resin, thereby enhancing the interfacial adhesion of the material. The thin film improves the mechanical properties and chemical stability of the material.
3. The low-warpage glass fiber reinforced nylon material according to claim 1, characterized in that: The nylon resin is one of PA6, PA66, PA56 or PA6 / 66, and the viscosity of the nylon resin is 1.8-2.
4.
4. The low-warpage glass fiber reinforced nylon material according to claim 1, characterized in that: The glass fiber is a combination of chopped glass fiber and milled glass fiber to provide enhanced mechanical properties and reduce warpage. The chopped glass fiber is used to improve the strength and rigidity of the material, and the milled glass fiber helps to improve the fluidity and processing performance of the material.
5. The low-warpage glass fiber reinforced nylon material according to claim 1, characterized in that: The coupling agent is a urea-based silane coupling agent to improve the interface bonding between the glass fiber and the nylon resin, thereby improving the overall performance of the composite material.
6. The low-warpage glass fiber reinforced nylon material according to claim 5, characterized in that: The processing aids are stabilizers S-EED, 1098, 168, H10, H318 and modified ethylene bis fatty acid amide TAF, silicone, erucic acid amide, stearate, EBS, and oxidized PE wax, so as to improve the processing performance and stability of the material.
7. The low-warpage glass fiber reinforced nylon material according to claim 1, characterized in that: The flame retardant is ammonium polyphosphate flame retardant DHPA-6621 or hypophosphite flame retardant FR701.
8. The low-warpage glass fiber reinforced nylon material according to claim 1, characterized in that: The temperature of the melt blending is 200-500°C.
Citation Information
Patent Citations
High-smoothness and high-strength nylon / organic long glass fiber composite and preparing method thereof
CN105623249A
High temperature resistant low warping nylon composite material of automobile engine hood shield and preparation method thereof
CN108102363A
Flame-retardant low-warping tin-soldering-resistant nylon glass fiber reinforced composite material
CN113943435A
Low-warpage high-toughness weather-resistant glass fiber reinforced nylon composite material and preparation method thereof
CN117866428A